2020
DOI: 10.18203/2349-3933.ijam20203599
|View full text |Cite
|
Sign up to set email alerts
|

A study of hepatobiliary involvement in adult patients with sickle cell disease

Abstract: Background: Sickle cell disease (SCD) encompasses a group of hemoglobinopathies characterized by a single amino acid substitution in the ß-globin chain. Hepatobiliary complications are frequent among sickle cell disease patients. Sickle cell disease has been extensively studied. However, data about hepatobiliary abnormalities among the adult age group are limited. Aim of our study aims to find the prevalence of hepatic-biliary involvement in Sickle cell disease in adult patients admitted to our hospital.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Similar to our study, Bokade et al, 3 in their study observed that yellowish discoloration was the most common presentation of patients, seen in 61.02% of patients, followed by abdominal pain in 37.4% of patients, fever in 28.71%, and vomiting in 23.58%. In another study, Mohanty et al, 4 studied 60 patients with SCD, and in their study, fever was the most common symptom at presentation seen in 83.3% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to our study, Bokade et al, 3 in their study observed that yellowish discoloration was the most common presentation of patients, seen in 61.02% of patients, followed by abdominal pain in 37.4% of patients, fever in 28.71%, and vomiting in 23.58%. In another study, Mohanty et al, 4 studied 60 patients with SCD, and in their study, fever was the most common symptom at presentation seen in 83.3% of patients.…”
Section: Discussionmentioning
confidence: 96%